Functional expression of two neuronal nicotinic acetylcholine receptors from cDNA clones identifies a gene family. - Boulter, J (1987)
A family of genes coding for proteins homologous to the alpha subunit of the muscle nicotinic acetylcholine receptor has been identified in the rat genome. These genes are transcribed in the central and peripheral nervous systems in areas known to contain functional nicotinic receptors. In this paper, we demonstrate that three of these genes, which we call alpha 3, alpha 4, and beta 2, encode proteins that form functional nicotinic acetylcholine receptors when expressed in Xenopus oocytes. Oocytes expressing either alpha 3 or alpha 4 protein in combination with the beta 2 protein produced a strong response to acetylcholine. Oocytes expressing only the alpha 4 protein gave a weak response to acetylcholine. These receptors are activated by acetylcholine and nicotine and are blocked by Bungarus toxin 3.1. They are not blocked by alpha-bungarotoxin, which blocks the muscle nicotinic acetylcholine receptor. Thus, the receptors formed by the alpha 3, alpha 4, and beta 2 subunits are pharmacologically similar to the ganglionic-type neuronal nicotinic acetylcholine receptor. These results indicate that the alpha 3, alpha 4, and beta 2 genes encode functional nicotinic acetylcholine receptor subunits that are expressed in the brain and peripheral nervous system.